2015
DOI: 10.1002/stem.2093
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide MicroRNA and Gene Analysis of Mesenchymal Stem Cell Chondrogenesis Identifies an Essential Role and Multiple Targets for miR-140-5p

Abstract: AbstractmicroRNAs (miRNAs) are abundantly expressed in development where they are critical determinants of cell differentiation and phenotype. Accordingly miRNAs are essential for normal skeletal development and chondrogenesis in particular. However, the question of which miRNAs are specific to the chondrocyte phenotype has not been fully addressed. Using microarray analysis of miRNA expression during mesenchymal stem cell chondrogenic differentiation and detailed examination of the role of essential different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
108
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(116 citation statements)
references
References 84 publications
(137 reference statements)
8
108
0
Order By: Relevance
“…Similarly, miR‐142‐3p has been reported to down‐regulate Wnt/β‐catenin signalling, which is largely in line with the central findings presented in this study 25. Moreover, Wnt signalling has been correlated to congenital diseases and cancers, as well as indicating that miR‐140‐5p plays a significant role in the regulation of Wnt signalling 20, 22. Mayorga et al 26 pointed out that miR‐145 expression could be used as a regulator of activity of β‐catenin in terms of hypoxia and ischaemia.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, miR‐142‐3p has been reported to down‐regulate Wnt/β‐catenin signalling, which is largely in line with the central findings presented in this study 25. Moreover, Wnt signalling has been correlated to congenital diseases and cancers, as well as indicating that miR‐140‐5p plays a significant role in the regulation of Wnt signalling 20, 22. Mayorga et al 26 pointed out that miR‐145 expression could be used as a regulator of activity of β‐catenin in terms of hypoxia and ischaemia.…”
Section: Discussionsupporting
confidence: 89%
“…Genome-wide and gene analysis identified that miR-140-5p plays an essential role in chondrogenic differentiation of MSCs 35. Recently, miR-140-5p gained a lot of attention for playing dual roles in both cartilage homeostasis and development 36, 37 by targeting RalA to enhance SOX9 and aggrecan (ACAN) 38 and showing potential for preventing OA 39, 40.…”
Section: Introductionmentioning
confidence: 99%
“…MiR-140-5p is essential for chondrogenic differentiation of MSCs, shown by analysis of genomes and genes, Tao et al overexpressed miR-140-5p in SMSCs and generated an improved version of exosomes (SMSC-140-Exos) that promoted chondrocyte proliferation and migration with less influence on the secretion of extracellular matrix. In an OA rat model, SMSC-140-Exos prevented OA [36,37]. Kim et al also used modified exosomes for RA [38].…”
Section: Therapeutic Potential Of Exosomes In Joint Diseasesmentioning
confidence: 99%